2021
DOI: 10.1093/jjco/hyab100
|View full text |Cite
|
Sign up to set email alerts
|

IMRT improves local control in patients with nasopharyngeal carcinoma compared with conventional radiotherapy: propensity score-matched analysis

Abstract: Background It is still controversial whether intensity-modulated radiotherapy has an obvious advantage over conventional radiotherapy. The purposes of this study were to evaluate prognostic factors in pre-treatment characteristics for nasopharyngeal carcinoma and to compare treatment outcomes in patients who received intensity-modulated radiotherapy and patients who received two-dimensional radiotherapy or three-dimensional radiotherapy. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…RT or RT-based comprehensive treatment is the most effective curative NPC treatment. With the extensive application of RT, especially IMRT, the local control and survival rates of NPC have been significantly improved, despite some failures primarily due to distant metastasis [ 3 , 32 , 33 ]. The present study investigated much higher five-year OS and DFS survival rates in the IMRT-treated group than in the untreated group (87.5% vs. 40.5% for OS and 84.2% vs. 37.8% for DFS).…”
Section: Discussionmentioning
confidence: 99%
“…RT or RT-based comprehensive treatment is the most effective curative NPC treatment. With the extensive application of RT, especially IMRT, the local control and survival rates of NPC have been significantly improved, despite some failures primarily due to distant metastasis [ 3 , 32 , 33 ]. The present study investigated much higher five-year OS and DFS survival rates in the IMRT-treated group than in the untreated group (87.5% vs. 40.5% for OS and 84.2% vs. 37.8% for DFS).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the 20% ine ciency, the calculated sample size was 75-296 cases, and 205 cases were actually included. The inclusion criteria of this study were as follows: (1) NPC patients were con rmed by pathology; (2) patients receiving radiotherapy; (3) patients ≥ 18 years old; (5) Voluntary participation in this study and informed consent. Exclusion criteria are as follows: Patients with other tumors, mental illness or serious organic disease.…”
Section: Study and Samplementioning
confidence: 99%
“…Because nasopharyngeal tumors show a high sensitivity to ionizing radiation [4] , patients with different disease stages should receive radiotherapy in their treatment plan in order to achieve the best therapeutic effect.Intensity Modulated Radiotherapy (IMRT) is the recommended radiotherapy method for NPC. Compared with traditional two-dimensional (2D) or three-dimensional (3D) radiotherapy, IMRT can provide high-dose radiation to NPC while protecting the adjacent important tissue structures [5] .Although with the continuous improvement of radiotherapy technology, the effect of IMRT can reduce the toxicity related to radiotherapy, the incidence of common toxic and side effects such as radiation dermatitis, oral mucositis and mouth di culty in patients receiving radiotherapy is still as high as 85%-100% [6][7][8][9] .Relevant studies have shown that the high incidence and aggravation of toxic and side effects will signi cantly affect the quality of life of patients and lead to the imbalance of treatment mentality and emotional anxiety of patients, thus affecting the degree of cooperation and enthusiasm of treatment [6] .…”
Section: Introductionmentioning
confidence: 99%
“…The increased adoption of IMRT, coupled with the systematic implementation of concurrent chemoradiotherapy, has greatly enhanced the treatment outcomes for nasopharyngeal carcinoma. As a result, the 5-year overall survival rate now stands at approximately 80% 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%